Density-independent mortality at early life stages increases the probability of overlooking an underlying stock–recruitment relationship. (7th February 2021) - Zimmermann, Fabian; Enberg, Katja; Mangel, Marc
Abstract: Beverton and Holt's (1957 . On the dynamics of exploited fish populations. UK Ministry of Agriculture, Fisheries and Food. Fisheries Investigations, 2: 533 pp.) monograph contributed a widely used stock–recruitment relationship (BH-SRR) to fisheries science. However, because of variation around a presumed relationship between spawning biomass and recruits, the BH-SRR is often considered inadequate and approached merely as a curve-fitting exercise. The commonly used and simplified version of the BH-SRR has eclipsed the fact that in their classic monograph, the derivation accounted for mechanistic recruitment processes, including multi-stage recruitment with explicit cohort-dependent and -independent mortality terms that represent competition between recruits and extrinsic, cohort-independent factors such as the environment or predation as two independent sources of mortality. The original BH-SRR allows one to recreate recruitment patterns that correspond to observed ones. Doing so shows that variation in density-independent mortality increases the probability of overlooking an underlying stock–recruitment relationship. Intermediate coefficients of variation in mortality (75–100%) are sufficient to mask stock–recruitment relationships and recreate recruitment time series most similar to empirical data. This underlines the importance of variation in survival for recruitment and that Beverton and Holt's work still provides a fundamental and useful tool to model the dynamics of populations.